A PROPOSED DESIGN OF ASSEMBLY LINE FOR CN-235 PLANE'S TAIL UNIT SUB-ASSEMBLY AT PT DIRGANTARA INDONESIA - SEKAR ROSANIA - (13413046), NURIFFA
PT Dirgantara Indonesia is the only one aeronautical company in Indonesia. Main product of the company is propeller engine plans. Product that will be focused in this research is CN-235 plan. In plan production process, component assembling process take most times. The component that has the most imbalance line is the tail unit. There are three parts of this component, LH horizontal, RH horizontal, and Vertical. The mean absolute deviation still showing poor value, which is 54,33 hours for LH horizontal, 48,76 hours for RH horizontal, and 64 hours for Vertical. Therefore, an ssembly line will be designed for balancing and smoothing the assemby line. Model that will be used in this research is mathematical model that developed into heuristic procedure by Rachamadugu and Talbot (1991). This model aimed to minimize the mean absolute deviation of aline. The procedure was adjusted to suit the needs and characteristics of the company. The adjustments are calculating the smoothness index, omitting average station time comparation, omitting task interchange, and checking the final station time towards cycle time. Input that will be needed to resolve this problem is task data, task processing time data, used jig data, operator data, and precedence diagam. The given solution results the repair of eight sub-assembly’s precedence diagrams and 30,7% as LH horizontal’s reduction of mean absolute deviation, 51,1% as RH horizontal’s, and 45,3% as Vertical’s.